Transcriptome Analysis of the Global Response of Pseudomonas fragi NMC25 to Modified Atmosphere Packaging Stress - Wang, Guangyu; Ma, Fang; Chen, Xiaojing; Han, Yanqing; Wang, Huhu; Xu, Xinglian; Zhou, Guanghong (Frontiers in Microbiology, 2018)
Pseudomonas fragi is usually isolated from chilled meats in relation to their spoilage, while many studies have shown that the application of modified atmosphere packaging (MAP) inhibits the spoilage potential of P. fragi. The effects of MAP on P. fragi NMC25 metabolism were determined in the present study by exposing this organism to different air conditions and comparing the resulting transcriptome profiles. We found 559 differentially expressed genes by RNA-seq, and the results revealed that MAP decreases the expression of genes involved in the electron transport chain (nuoAB), resulting in an inhibition of aerobic respiration. Meanwhile, MAP also induced the downregulation of genes responsible for ATP-binding cassette transporters, flagellar and type I fimbrial proteins, and DNA replication and repair, which may further influence nutrient uptake, motility, and growth. In addition, NMC25 cells modified their pathways for energy production, amino acid synthesis, membrane lipid composition and other metabolic patterns to adapt to MAP. These data show that P. fragi NMC25 survives under MAP but reduces part of its metabolism related to its spoilage ability.